Alpha-synuclein phosphorylation role on Parkinson’s disease - Silva, Filipa Magalhães, 1990- (2013)
Tese de mestrado. Biologia (Biologia Molecular e Genética). Universidade de Lisboa, Faculdade de Ciências, 2013